Optimizing the Assessment of Qawa’id Materials by Utilizing Wordwall Media - Erlina, Erlina; Ainin, Moh.; Rosyidi, Abdul Wahab; Zulpina, Zulpina; Lando, Natalia S. (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research was initiated by the apprehension experienced by students in qawa’id material tests and the lack of digital-based media, especially qawa’id assessments. The primary objectives of this study were to create an assessment tool based on Wordwall media for evaluating qawa’id material, to depict the assessment environment before and after the implementation of this media and to evaluate the feasibility and usability of the product. The data were collected through interviews with Arabic language teachers in MAN 2 Payakumbuh, 35 tenth grade students in the second semester of the 2023/2024 academic year, and questionnaires for expert validation and student responses. The findings of this study indicated that : 1). There was a noticeable contrast in the atmosphere of qawa’id test activities before and after the utilization of Wordwall media-based assessment tools, leading to a reduction in students’ apprehension. 2). After conducting a structured research stage, according to linguists and media experts, the product was considered feasible with a percentage of 80% and very feasible with 99% and 85%. 3). Teachers and students found the product to be highly practical, with an acceptance rate of 85.13%. The integration of Wordwall in the qawa’id assessment process served as a strategy to alleviate student apprehension during qawa’id assessments. Qawa’id assessment based on Wordwall media developed in this study was both feasible and practical to be implemented by Arabic language teachers for tenth-grade students in the second semester.